OP08 Assessing models of ACP in primary care, the meta-larc trial: part 2 engaging patient and family advisors in research. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Totten, A; Combe, A; Minitti, M; Dokken, D; Simpson, M; Siddiqui, R
Abstract : Background: Patient and family engagement is essential to community-based pragmatic research. After our study of advance care planning (ACP) in primary care was funded, we expanded the proposal and developed a detailed Engagement Plan (EP) to accompany the study protocol. Methods: We established a cohort of 11 Patient and Family Advisors (PFA) to guide the project; seven associated with participating PBRNs and four unaffiliated or at-large PFAs (2 US; 2 Canadian). During project initiation, the joint coordinating center established a working committee to develop an EP using the PCORI template. We surveyed PFAs about goals, solicited feedback from PBRNs and engagement experts, distributed planning assignments, and shared drafts with stakeholders. Results: The EP was developed based on a quality improvement approach in which monitoring, measuring and improving engagement is the focus. Monitoring engagement includes baseline assessment of needs, quarterly surveys and annual check-ins. Engagement measurement tracks stakeholder inputs and resulting impact on the project and establishes processes to support participant recruitment and retention. PFA-identified goals form QI targets and inform strategies to clarify expectations, forms of participation, and documenting and communicating the impact of PFA contributions. The EP will be updated twice annually. Conclusion: Creating a formal EP allowed operationalization of our commitment to PFA engagement and integration into multiple aspects of the study. Making the plan a living document allows us to identify challenges, address issues, and document our experience. Approaching engagement as a component of trial design and execution facilitates development of best practices and science around engagement.